Phototreatment of Water by Organic Photosensitizers and Comparison with Inorganic Semiconductors - Merlyn Thandu; Clara Comuzzi; Daniele Goi (International Journal of Photoenergy)
Phototreatment of water is drawing the attention of many as a promising alternative to replace methods like chlorination, ozonization, and other oxidation processes, used in current disinfection methods limiting harmful side-products and by-products that can cause damage to the fauna and flora. Porphyrins, phthalocyanines, and other related organic dyes are well known for their use in photodynamic therapy (PDT). These photosensitizers cause cell death by generating reactive oxygen species (ROS) especially singlet oxygen in the presence of light. Such molecules are also being explored for photodynamically treating microbial infections, killing of unwanted pathogens in the environment, and oxidation of chemical pollutants. The process of photosensitisation (phototreatment) can be applied for obtaining clean, microbe-free water, thus exploiting the versatile properties of photosensitizers. This review collects the various attempts carried out for phototreatment of water using organic photosensitizers. For comparison, some reports of semiconductors (especially TiO2) used in photocatalytic treatment of water are also mentioned.